Students’ Perception of English Learning Difficulties and Strategies - Fetty Poerwita Sary Sary (Journal of ELT, Linguistics, and Literature, 2015)
English is considered as important in this era, especially towards the implementation of the ASEAN free market known as the ASEAN Economic Community by the end of 2015, which means that competition in the job market will increase. Many universities open their international class to facilitate the need of prospective students (senior high school graduates). In fact, there are still problems facing by the students in learning English as a tool to understand other courses. Therefore, the research is aimed to know students’ perception of the difficulties they encounter in learning English as a foreign language, also the reasons underlying these difficulties, and strategies they use in accomplishing their linguistic tasks. This study used two questionnaires that are distributed to 45 new students of International ICT Business class, Telkom University Bandung Indonesia. The results showed that the 98% of respondents said that they have problem in English especially grammar. It was due to their lack of knowledge of the English linguistic rules, and they made use of various strategies; social and affective strategies mainly.